(untitled) (Homoeopathy for All, 2021)
The word haemorrhoid is derived from the Greek word haema means blood and rhoos means flowing.1 Haemorrhoids are commonly known as piles. Haemorrhoids are distal displacement and prolapse of the haemorrhoidal cushions, distension of the haemorrhoidal arterio-venous anastomoses, or dilation of the veins of the internal haemorrhoidal venous plexus resulting from deterioration of anchoring connective tissue.2 It is most common among the age between 45-65.3 Data on the prevalence of haemorrhoids are very scarce. However, data study done in 2008 and 2009 on 976 participants shows that 38.93% of them were suffering from haemorrhoids. 72.89% patients had grade I, 18.42% had grade II and 8.16% had grade III, and only 0.53% had grade IV stage haemorrhoids. From the study, it is also concluded that 44.74% patients complaints about the pain whereas 55.26% had no pain.4Depending upon the severity, haemorrhoids are divided into 4 grades. Grade 1 is initial stage, where it bleeds or itches but no prolapse. In Grade II, where mass of haemorrhoid start to protrude from anal opening during defecation but goes back in on completion.